Beyond the age of oil : the myths, realities, and future of fossil fuels and their alternatives - Maugeri, Leonardo, 1964- (Santa Barbara, Calif. : Praeger, 2010)
This book offers a revealing picture of the myths and realities of the energy world by one of our energy experts and managers. The transition from a world economy based on fossil fuels to one based on sustainable energy sources must take place between now and 2035 to avert unacceptable environmental consequences, but this dauntingly difficult transition will only happen if the community of nations can couple a massive phase in of alternative energy sources with fossil fuel efficiency improvements. At the end of the first decade of the 21st century, the human race finds itself caught in an "energy trap." Carbon rich fossil fuels, coal, petroleum and natural gas, are firmly entrenched as the dominant sources of our energy and power. Their highly concentrated forms, versatility of use, ease of transport and storage, ready availability, and comparatively low costs combine to give fossil fuels an unassailable competitive advantage over all alternative sources of energy. This economic reality means that fossil fuels will inevitably continue to be the backbone of the global economy for the next quarter of a century, even while the adverse climate and environmental effects of our dependence on fossil fuels hurtle toward global crisis levels. To avert unacceptable environmental consequences, the world must deliberately and incrementally supplant fossil fuels with alternative energy sources, on a schedule that will have them overtake fossil fuels in the world's energy budget by 2035. To achieve this urgent goal without massive economic dislocation and reduction in standards of living, global investment in fossil fuel efficiency will be just as important as the development and massive deployment of alternative energy technologies and delivery systems.
In this eagerly awaited sequel to his prize-winning bestseller, The Age of Oil, Leonardo Maugeri, the strategy director of one of the world's biggest energy companies, puts forward a hard-headed, concrete plan in simple everyday language for how to shift the world economy's primary energy dependence from fossil fuels to renewable energies by 2035. Assuming no specialized knowledge, the author walks the reader chapter by chapter through each of the fossil fuels (oil, coal, and natural gas) and each of the alternative energy sources (nuclear, hydroelectric, biofuel, wind, solar, geothermal, and hydrogen). Drawing on the unparalleled data and analysis resources at his command, Dr. Maugeri assesses the problems and advantages of each energy source in turn in order to constrain the optimal mix of energy sources that the world should be aiming for in 2035. Critically, he lays out the arduous path for getting from here to there. Dr. Maugeri shows that next 25 years will be a rocky marriage between the old and the new energy paradigms, during which we must dramatically improve the efficiency of our continuing use of fossil fuels, while driving ahead on all fronts to an energy future based on a suite of sustainable energy sources.
Introduction : all the energy in the world -- The fossil sources. "King" oil ; The splendor and misery of coal ; All that gas ; The quest to eliminate carbon dioxide -- The alternatives. Nuclear power : renaissance or decline? ; The weight of water ; Biofuels : behind the smoke and mirrors ; Gone with the wind? ; The sun also rises ; Geothermal power : the primitive energy of the earth ; The hype about hydrogen, the hope about electric cars ; Energy efficiency : the invisible source of energy -- Conclusions : how can we escape our energy trap?
Originally published in Italian: [Milan, Italy] : Sperling & Kupfer, c2008.
Revised by author.
Includes bibliographical references and index.
Keywords: Power resources; Renewable energy sources; Petroleum reserves -- Forecasting; Energy industries; Energy policy